Hiscock, Sarah. Interview about the Hazel Pearl, how to make gun shells, and growing up in Champney's West. - Barrett, Terra (2016)
Interview with Sarah Hiscock of Champney's West, NL about the wreck of the Hazel Pearl, growing up in the community, and how to make gun shells. Sarah Hiscock Long was born December 15, 1933 in Champney’s West where she grew up until she moved to Champney’s East at the age of 18 when she married Harold Walters; Hiscock lived in Champney’s East for 65 years and raised her family there; 1:57 – Hiscock’s memory of the sinking of the Hazel Pearl; discussion of shipping salt fish; 6:37 – growing up in Champney’s West; going to school; playing games; explanation of King William; 9:31 – spelling contest in school; 10:35: description of the Hazel Pearl; 13:39– discussion of the fun Hiscock had growing up in Champney’s West; working in service; her family; community entertainment; growing vegetables in a garden; keeping animals; changes in the community; 20:46 – explanation of making gun shells with the tools at the Heritage House; 25:30– discussion of what animals were shot with the gun shells; preparing birds to eat; 27:40 – difference in chores and cleaning when Hiscock was growing up and 2016; making diapers; hauling water.